1984
DOI: 10.1099/0022-1317-65-3-651
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis B Virus DNA in Pancreas, Kidney and Skin of Two Human Carriers of the Virus

Abstract: SUMMARYUsing the Southern blot technique, we have analysed the presence and state of hepatitis B virus (HBV) DNA in non-hepatic tissue from two human HBV carriers. HBV DNA sequences were detected in the pancreas, kidney and skin, demonstrating HBV infection of these organs. Moreover, the restriction DNA patterns were consistent with the integration of these viral sequences into high molecular weight DNA. These results demonstrate that HBV infection is not restricted to the liver.Hepatitis B virus (HBV) infects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
2
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(104 citation statements)
references
References 10 publications
1
100
2
1
Order By: Relevance
“…There are some studies indicating that HBV antigens and viral DNA can be detected in pancreatic tissue, demonstrating HBV infection of these organs. 18,33,34 Replicative forms of HBV nucleic acids were identified in the pancreas in patients with acute HBV infection. 35,36 HBsAg was detected in pure pancreatic juice and bile in patients with acute and chronic HBV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some studies indicating that HBV antigens and viral DNA can be detected in pancreatic tissue, demonstrating HBV infection of these organs. 18,33,34 Replicative forms of HBV nucleic acids were identified in the pancreas in patients with acute HBV infection. 35,36 HBsAg was detected in pure pancreatic juice and bile in patients with acute and chronic HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from previous study indicated that HBV DNA sequences were detected in the pancreas, kidney and skin, demonstrating HBV infection of these organs. 18 Anatomically, liver and pancreas share common ducts and blood vessels may make the pancreas another potential target organ for infection with HBV. Nevertheless, epidemiological data investigating the relationship between infection with HBV and pancreatic cancer have shown inconsistent results so far.…”
mentioning
confidence: 99%
“…Replication of the viral genome and production of the 42-nm virion in infected liver tissues are frequently observed. However, the viral DNA and proteins have also been detected in many other tissues, including kidney, spleen, pancreas, bone marrow, and circulating blood cells (16,31,41,45). Furthermore, viral genes, including both the surface and the core genes, can be expressed in cultured systems of heterologous tissue type (18,46,49).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies find that hepatitis B virus can replicate in human pancreatic tissue and that patients with hepatitis B infection have impairments of pancreatic function (Hoefs et al, 1980;Yoshimura et al, 1981;Dejean et al, 1984;Katakura et al, 2005). Also, some cohort and case-control studies (de Gonzalez et al, Lei Li 1,3 , Bo Wu 2 , Li-Bo Yang 3 , Guan-Cheng Yin 3 , Ji-Yong Liu 1 * 2008; Hassan et al, 2008;Iloeje et al, 2009;Gordon et al, 2009;Hong et al, 2010;Zhu et al, 2011;Wang et al, 2012;Ben et al, 2012) have been conducted to estimate the relationship between chronic hepatitis B virus infection and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%